Side effects of AZD 1222 COVISHIELD vaccine among front-line health care workers in a tertiary care hospital: A descriptive cross-sectional study - Poudel, Nimesh; Mishra, Navin Kumar; Bhattarai, Mahesh; Shah, Rakesh Kumar; Dhungel, Alok; Karna, Rohit; Dhakal, Subodh Sagar (Journal of Gandaki Medical College-Nepal, 2023)
Introduction: Coronavirus disease vaccination has been accepted as a global health measure to prevent severity,transmission and mortality. Vaccine frequently cause adverse effects which is supposed to be due to protective immune response induced by the vaccine. The study aimed to find out the prevalence of side effects of first dose of AZD 1222 COVISHIELD vaccine among front line health care workers receiving vaccination in a tertiary care hospital.Methods: This was a descriptive cross-sectional study among front line health workers who received the first dose of COVISHIELD vaccine. The study was conducted from February 2021 to March 2021 in a tertiary care hospital after receiving ethical approval from the Institutional Review Committee. Convenience sampling was used for data collection and data was analyzed using SPSS version 17 was used for analysis. Point estimate at 95% confidence interval was calculated along with frequency and proportion for binary data.Results: Among 629 participants, 344(54.7%) participants reported one or other side effects following vaccination. The major side effects reported were fever 152(19.6%), myalgia 144(22.9%), pain at injection site 123(19.6%), headache 75(11.9%) and in one reactivation of Herpes Zoster.Conclusions: After the first dose of COVISHIELD vaccine, mild symptoms were seen which resolved within few days. Some cases of reactivation of Herpes Zoster was found. The adverse effects were seen more in patients who had history of COVID-19 infection.